Effects of pressurized liquid extraction with dimethyl sulfoxide on the recovery of carotenoids and other dietary valuable compounds from the microalgae Spirulina, Chlorella and Phaeodactylum tricornutum. (30th March 2023) - Wang, Min; Morón-Ortiz, Ángeles; Zhou, Jianjun; Benítez-González, Ana; Mapelli-Brahm, Paula; Meléndez-Martínez, Antonio J.; Barba, Francisco J.
Highlights: Pressurized liquid extraction (PLE) + H2 O increased protein yield of Chlorella. PLE + DMSO (over 30 %) increases the polyphenol yield compared to control. Significant increase in pigment yield of PLE + DMSO (higher than 50 %) vs control. Great differences in mineral recovery depending on the microalgae species. Abstract: The impact of pressurized liquid extraction (PLE) and DMSO concentration (0, 30, 50, 100 %) on the yield of antioxidants and minerals from Chlorella were investigated. The results showed that PLE increased the antioxidant yield. Water extracted more proteins, while with 100 % DMSO more polyphenols, chlorophylls, and carotenoids were obtained. The efficiency coefficient (KPLE ) results showed that PLE + 100 % DMSO was more suitable for the recovery of antioxidants and pigments from Chlorella (polyphenols 10.465 mg/g, chlorophyll a 6.206 mg/g, chlorophyll b 3.003 mg/g, carotenoids 0.971 mg/g). Thus, PLE + 100 % DMSO was used for recovery studies on Spirulina, Chlorella, and Phaeodactylum tricornutum . Fucoxanthin, β-carotene, zeaxanthin, and lutein were the major carotenoids in P. tricornutum, Spirulina, and Chlorella, respectively. Regarding the extraction of minerals, Relative Nutrient Values results were calculated based on Recommended Dietary Allowances. The results indicated that the extracts could be used as a mineral source for different populations.